2014
DOI: 10.1038/nmat4135
|View full text |Cite
|
Sign up to set email alerts
|

Layered memristive and memcapacitive switches for printable electronics

Abstract: Novel computing technologies that imitate the principles of biological neural systems may offer low power consumption along with distinct cognitive and learning advantages. The development of reliable memristive devices capable of storing multiple states of information has opened up new applications such as neuromorphic circuits and adaptive systems. At the same time, the explosive growth of the printed electronics industry has expedited the search for advanced memory materials suitable for manufacturing flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
401
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(411 citation statements)
references
References 33 publications
6
401
2
2
Order By: Relevance
“…In addition, the threshold voltages to switch the conductance of the device were shown to be state-dependent, which emerges from the interplay of a memristance with a memcapacitance. In contrast to other realizations of memristors, [47][48][49] memristance and memcapacitance switching of the presented device are observed between different terminals. The memristance is measured in the two-terminal geometry and the memcapacitance between the lateral gates and the wire.…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, the threshold voltages to switch the conductance of the device were shown to be state-dependent, which emerges from the interplay of a memristance with a memcapacitance. In contrast to other realizations of memristors, [47][48][49] memristance and memcapacitance switching of the presented device are observed between different terminals. The memristance is measured in the two-terminal geometry and the memcapacitance between the lateral gates and the wire.…”
Section: Discussioncontrasting
confidence: 72%
“…Two-dimensional (2D) layered van der Waals (vdW) materials, such as MoS 2 and WS 2 , are considered to be promising electrolytes for use in extremely thin CBRAM devices because they can be exfoliated to atomic layers. Recently, Bailey et al reported ion migration-based synaptic memristor devices containing 2D layered vdW materials 17 . Their surface oxide layers with a subnanometer thickness exhibited an excellent synaptic plasticity and learning capacity in response to~100-mVlevel stimuli comparable to neuron spikes, which is thought to result from the formation of electrically induced conductive bridges consisting of oxygen vacancies 17 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, their usage has also been demonstrated to improve the stability of organic 6 and perovskite 7 solar cells, as well as of organic light emitting devices. 8 Other applications based on MoO x films, such as gas and chemical sensors [9][10][11] and storage devices such as memristive, memcapacitive 12 and Lithium-ion 13 devices were also reported recently.…”
Section: Introductionmentioning
confidence: 99%